Adapted tool design for the cold forging of gears from non-ferrous and light metals - Rohrmoser, Andreas; Hagenah, Hinnerk; Merklein, Marion (International Journal of Advanced Manufacturing Technology, 2021)
Due to growing competitive pressure within the manufacturing sector, there have been increasing attempts to establish resource saving production methods in gear manufacturing within recent years. Cold forging offers the potential—in addition to a high material and energy efficiency—to produce gears with an excellent surface quality, increased hardness as well as a load adapted fiber orientation. With regard to the wide range of applications there is a broad demand for gear materials, ranging from high-strength steels to non-ferrous and light metals. The flow behavior of the material has a significant influence on the cold forging process. Therefore, no consistent process result is achieved when forming different materials. Challenges exist due to deficient die filling and poor resulting geometrical accuracy. In this contribution, material-specific challenges during the full forward extrusion of gears from non-ferrous and light metals have been identified and suitable tool-sided measures were derived. A validated numerical process model was used to determine the underlying mechanisms of action and to verify the derived measures. A reduced yield stress leads to inflow formation, insufficient die filling, and low achievable strain hardening, as well as gearing accuracy. The tool-sided measures achieved a significant increase of resulting die filling and gearing accuracy as well as the mechanical properties. That provides the basis for the production of ready-to-use gears from various metal materials.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cold forging; Gears; Light metals; Simulation; Tool design